2005
DOI: 10.1016/j.technovation.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring new websites to appeal to those most likely to shop online

Abstract: This study extends the conventional wisdom concerning how a commercial website can be configured to attract online shoppers, and specifically, initial shoppers. Based on past research [Inform. Syst. Res. 13 (2002) 187] and theory [Diffusion of Innovations (1995)], a number of 'form' and 'substantive' website features were assessed as to their attractiveness to consumers of varying (a) Internet experience and (b) innovativeness. A self-administered survey was completed by a convenience sample of 363 residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 41 publications
2
40
0
2
Order By: Relevance
“…Research extensively examines the relationship between website elements and their influence on usage intentions, online behavior, and overall system satisfaction (e.g., Bauer, Falk, & Hammerschmidt, 2006;Bauer, Hammerschmidt, & Falk, 2005;Blake, Neuendorf, & Valdiserri, 2005;Dickinger & Stangl, 2013;Floh & Treiblmaier, 2006;Gan, Clemes, Limsombunchai, & Weng, 2006;Torkzadeh & Dhillon, 2002). Dennis, Merrilees, Jayawardhena, and Wright (2009) introduce the term "web atmospherics" to describe the web design elements that constitute the primary drivers of online behavior.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Research extensively examines the relationship between website elements and their influence on usage intentions, online behavior, and overall system satisfaction (e.g., Bauer, Falk, & Hammerschmidt, 2006;Bauer, Hammerschmidt, & Falk, 2005;Blake, Neuendorf, & Valdiserri, 2005;Dickinger & Stangl, 2013;Floh & Treiblmaier, 2006;Gan, Clemes, Limsombunchai, & Weng, 2006;Torkzadeh & Dhillon, 2002). Dennis, Merrilees, Jayawardhena, and Wright (2009) introduce the term "web atmospherics" to describe the web design elements that constitute the primary drivers of online behavior.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Website appeal refers to the quality of a website's perceptual features to generate user interaction [12], and persuade online shoppers towards a site [11]. An appealing website is more likely to attract visitors, stimulate positive purchase intentions, and establish higher standards of trust and usability [28], [75], [94], [122], [128].…”
Section: Website Appealmentioning
confidence: 99%
“…Utilitarian consumer behavior has been described as ergic, task related, and rational (Batra and Ahtola 1991). Blake et al, (2005) suggested that utilitarian values has strong impact on online commerce. Online shoppers are more concerned about Utilitarian value (Blake et al, 2005;Mart铆nez-L贸pez et al 2014, Bernardo 2012, Beldona et al, 2011.Utilitarian motivated consumers seeks specific information whereas hedonically motivated consumers seek general information (Paden & Stell 2010).They are utilitarian shoppers, looking for functional product benefits.…”
Section: Utilitarian Motivation In Online Contextmentioning
confidence: 99%